Математичне обґрунтування технологічного процесу роботи качановідокремлювального апарату багатофакторної дії - Думенко, К. М.; Бондаренко, О. В.; Філімоніхін, Г. Б.; Кулєшков, Ю. В.; Dumenko, Konstantin; Bondarenko, Alexander; Filimonihin, Genadiy; Kuleshkov, Yuriy (КНТУ, 2015)
У роботі проведені дослідження основних способів відокремлення качанів від стебел. Розроблена математична модель процесу відокремлення качанів при поєднанні багатьох сил, яка дає можливість встановити закономірності зміни основних кінематичних параметрів качановідокремлювального апарату багатофакторної дії. На підставі отриманих рівнянь визначенні шляхи подальшого розвитку кукурудзозбиральної техніки нового покоління. The aim is to study work pick plate separation machine heads by developing a mathematical model of the process separation heads at complex combination of several forces. In the work study the basic methods of separating the cobs from the stalks. Developed a mathematical model the process of separating the cobs with a combination of many forces, which gives you the opportunity to establish patterns of changes in the basic kinematic parameters of the picking machine multifactorial action. Based on these equations are defined ways further development of corn-harvesting technical new generation. As a result of the research means separation of ears basic mathematical model separation machine heads the combination of many forces, which makes it possible to change the basic patterns of kinematic parameters separation machine heads multi-unit action.
Mathematical justification of technological process work of corn picker multifactor action
Keywords: протягувальні вальці; стриперні пластини; качановідокремлювальний апарат; stretch rollers; pick plate; separation machine heads